KUALITAS PELAYANAN DAN PROMOSI MEMPENGARUHI KEPUTUSAN MAHASISWA DALAM MEMILIH KULIAH DI PERGURUAN TINGGI - Syamsudin Baharsyah; Nurhasan Nurhasan; Rico Septia B (Program Studi PGSD Universitas Flores, 2023)
The decline in service quality standards and promotions carried out by tertiary institutions are two of several factors causing a decrease in student acquisition, this is what influences student decisions in choosing college. This prompted researchers to prove that there was an influence from these two factors, so this research was conducted with the aim of knowing and analyzing the quality of service and promotion, their simultaneous influence on student decisions in choosing to study at college. The analytical method used in this research is multivariate with correlation or multiple regression. The number of samples in this study was 30 times the number of variables studied, 90 respondents. The data collection method in this research was carried out by filling out a questionnaire distributed via the Googleform application. This research resulted in the following findings: Service quality and promotion affect 69.8% of student decisions in choosing to study at a university. Based on these findings, it is recommended that universities improve and improve service quality and promotion factors.